The last of the Bonegilla girls - Purman, Victoria (Sydney, NSW : HQ Fiction, 2018)
1954: When sixteen-year-old Hungarian Elizabeta arrives in Australia with her family, she is hoping to escape the hopelessness of life as a refugee in post-war Germany. Her first stop is the Bonegilla Migrant Camp on the banks of the Murray in rural Victoria, a temporary home for thousands of new arrivals, all looking for work and a better life. There, Elizabeta becomes firm friends with three other girls. The Bonegilla girls rush together towards a life that seems full of promise, even as they cope with the legacy of war, the oppressive nature of family tradition and ever-present sorrow. So when a ghost from the past reaches out for Elizabeta and threatens to pull her back into the shadows, there is nothing that her friends wouldn't do to keep her safe.
Keywords: Bonegilla Migrant Reception Centre -- Fiction; Friendship -- Fiction; Sisters -- Fiction; Families -- Fiction; Interpersonal relations -- Fiction; Australian fiction; Female friendship -- Fiction; Immigrants -- Australia -- Fiction; Secrecy -- Fiction; Victoria -- History -- 20th century -- Fiction; Australian; Historical fiction